Online Booking Application for Long-Distance Train Ticket Adapted to the Covid-19 Protocol - Diah Asih Relawanti; Yopi Mahangga Ujung; Rossy Yanuar Pradania; Andi Nugroho; Achmad Kodar (LPPM Universitas Islam 45 Bekasi, 2022)
Train is favorite transportation in Indonesia. The increase in the number of passengers from year to year is proof that rail transportation supports community mobility. Therefore, services are needed to accommodate the needs of the community in ordering train tickets. Currently, the train ticket booking system can be done offline or online. Especially for the online train ticket booking system, there are still some obstacles i.e., during the Covid-19 pandemic, a train ticket booking information system is also needed which must be adjusted to health protocols to minimize the spread of Covid-19 during travel by train, starting from the ticket booking process. The system development methodology used is Scrum, this methodology is a framework that applies the stages of planning, analysis, design and implementation to build or develop software where work is divided into time frames called sprints. The long-distance train ticket booking application has been able to minimize the accumulation of passengers in exchanging tickets at the train station platform.